2013
DOI: 10.7314/apjcp.2013.14.11.6883
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Radiotherapy with Concurrent Weekly Cisplatin in Locally Advanced Head and Neck Cancers of Squamous Cell Origin - a Single Institution Experience

Abstract: Background: Platinum based concurrent chemo-radiation is the de-facto standard of care in the non-surgical management of locally-advanced head and neck cancer of squamous origin. Three-weekly single agent cisplatin at 100 mg/m 2 concurrent with radical radiotherapy has demonstrated consistent improvement in loco-regional control and survival. This improvement is however at the cost of considerable hematologic toxicity and poor overall compliance. The routine use of this regime is improbable in developing count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 25 publications
(42 reference statements)
2
10
0
Order By: Relevance
“…A study reported that liver lesions could be boosted to a total of 83 Gy (Lausch et al, 2013). We found that conventional fraction intense-modulated radiotherapy reduced liver damage and encouraged more normal cell regeneration than hyperfractioned radiotherapy, according to radiation biology (Dimri et al, 2013). The use of IMRT may improve the ability to deliver high doses to the planned target volume while preserving the integrity of the surrounding normal tissues (Xiang et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…A study reported that liver lesions could be boosted to a total of 83 Gy (Lausch et al, 2013). We found that conventional fraction intense-modulated radiotherapy reduced liver damage and encouraged more normal cell regeneration than hyperfractioned radiotherapy, according to radiation biology (Dimri et al, 2013). The use of IMRT may improve the ability to deliver high doses to the planned target volume while preserving the integrity of the surrounding normal tissues (Xiang et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Cisplatin (cis-diamminedichloroplatinumⅡ, CDDP) is one of the main chemotherapeutics, which is widely used for the treatment of various malignant solid tumors such as ovarian, lung, testicular and head and neck cancers (Pfister et al, 2010;Dimri et al, 2013; Dua et al, 2013;Besse et al, 2014 …”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown the effectiveness and feasibility of chemotherapy for cancers species involving the lung, pancreas, liver, large intestine, and so on. Conversely, treatment with anticancer drugs can also do harm to patients' normal tissues and organs, and those toxicities may lead to a worsened quality of life and shortened survival.Cisplatin (cis-diamminedichloroplatinumⅡ, CDDP) is one of the main chemotherapeutics, which is widely used for the treatment of various malignant solid tumors such as ovarian, lung, testicular and head and neck cancers (Pfister et al, 2010;Dimri et al, 2013; Dua et al, 2013;Besse et al, 2014 …”
mentioning
confidence: 99%
“…Similar findings were reported by Dimri et al .,[ 36 ] who reported 188, Stage III/IV, treatment naive HNSCC patients (excluding nasopharynx and paranasal sinus) treated with weekly CDDP 35 mg/m 2 and RT to the dose of 60–66 Gy (at 2 Gy/fraction, 5 fractions per week).…”
Section: Role Of Chemotherapy In Head-neck Squamous Cell Carcinoma – mentioning
confidence: 99%